2020
DOI: 10.1021/acsami.0c12647
|View full text |Cite
|
Sign up to set email alerts
|

2D Hexagonal Boron Nitride-Coated Cotton Fabric with Self-Extinguishing Property

Abstract: Here, we report on the fabrication of flame retardant hydrophobic cotton fabrics based on the coating with two-dimensional hexagonal boron nitride (2D hBN) nanosheets. A simple one-step solution dipping process was used to coat the fabrics by taking advantage of the strong bonding between diethylenetriamine and hBN on the cotton surface. Exposure to direct flame confirmed the improvement of the flame retardant properties of the coated cotton fabrics. In turn, removal of the flame source revealed self-extinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Hexagonal boron nitride (h-BN) is a graphene-like compound with an isoelectronic structure. 27,28 The high thermal conductivity 29 (200-600 W/Mk) and excellent thermal stability 30,31 are of great interest to experts and scholars. These excellent properties make it possible to prepare new PBS flame-retardants 32 with other flameretardants.…”
Section: Introductionmentioning
confidence: 99%
“…Hexagonal boron nitride (h-BN) is a graphene-like compound with an isoelectronic structure. 27,28 The high thermal conductivity 29 (200-600 W/Mk) and excellent thermal stability 30,31 are of great interest to experts and scholars. These excellent properties make it possible to prepare new PBS flame-retardants 32 with other flameretardants.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the extremely high thermal stability promotes the application of BN nanosheets in some special fields . For example, the layered structure and thermal stability have made BN nanosheets the ideal nanofillers in flame-retardant polymer composites. , It is found that BN nanosheets effectively suppress the delivery of heat and mass between fire and a polymer by building a robust defense layer . However, it has been realized gradually that the fire hazards of polymer composites do not consist of merely heat but also include toxic smoke particles. , Due to the lack of metal elements and a large band gap, the toxic smoke suppression of BN nanosheets with a low catalysis effect leaves much to be desired …”
Section: Introductionmentioning
confidence: 99%
“…10 For example, the layered structure and thermal stability have made BN nanosheets the ideal nanofillers in flame-retardant polymer composites. 11,12 It is found that BN nanosheets effectively suppress the delivery of heat and mass between fire and a polymer by building a robust defense layer. 13 However, it has been realized gradually that the fire hazards of polymer composites do not consist of merely heat but also include toxic smoke particles.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the above two methods, coating is another effective flame‐retardant method 11 . This method is often used for flame‐retardant fabrics, 12,13 and some researchers have applied it to flame retardance of polyurethane foam 14 . Wang et al 15 studied synthetic silicone resin (poly‐DDPM) and expandable graphite (EG) mixed coating to RPUF that gave RPUF excellent flame‐retardant properties.…”
Section: Introductionmentioning
confidence: 99%